Semiotics of Mirror-tile Artwork Decoration in Iranian-Islamic Architecture - Sepehri, Naeim (Enquiry The ARCC Journal for Architectural Research, 2024)
Mirror-tile geometric Artwork is considered the last innovation of Iranian artists in the group of the fine arts. That utilizes, for the interior architecture and decoration of buildings. The use of pieces of glass-mirrors and Mirror-tile artwork has economic origins and recycling roots. In the beginning, the Glass-mirrors, which had been brought to Iran from Europe, break during transportation. Iranian artists and Muslim Craftsmen found an innovative way to take advantage of these broken pieces and used them as Mirror-tiles. Being wasteful is an act that is abhorred in Islam. In traditional Iranian-Islamic art, the mirror element, besides that has been one subject of aesthetics for decorating the architectural built-space, includes deep cultural concepts that have not been considering for various reasons. This research looks at semiotic signs from an analytical point of view and explaining the use of the Mirror-tile art in Iranian-Islamic architecture by quoting information from the analysis to understand the quality of architectural built-space decorated with the Mirror-tile art. Aim to introduce the real and genuine aspects of mirror art as an influential architectural element through the thoughts of its creators as a result, in this research, first, the concepts related to semiotic ideas are dealt with descriptively, and, with an analytical approach, a connection established between various theories. Mirror-tile art also contains tremendous amounts of meaning - messages that words can never describe. For these craftsmen, that’s at the core of their creation. Among the mystics, the inner language is the language of Spirit and Truth, and the tools of that language are the symbol and indication. With the aim of the influence of the Persian mystical thoughts about the mirror, this study cum the available historical and contemporary sources and analyzing them deals with the hidden meanings in Mirror-tile artwork. Reveal its connection with mystical thoughts through Persian literature.